A Study On Clinical Profile Of Patients With Complete Acl Tear Admitted At A Tertiary Care Hospital - Dr Mahesh Kumar Reddy Vuruvakili, Dr. Atithi Vijay K V (Cuestiones de Fisioterapia, 2024)
Analysis of knee motion in a horizontal plane reveals a different type of motion that of internal femoral condylar motion with terminal knee extension. This is called "Screw Home" mechanism which offers greater stability. This mechanism is due to the inequality of bony geometry between femoral condyle and tibial plateau. Detailed history about the trauma and mode of injury was taken in the casualty/OPD. Case history was recorded in a specially designed Case Record Form (CRF) by taking history of illness and by doing detailed clinical and radiological examination and relevant investigations. Finally, after the diagnosis, patients were selected for the study depending on the clinical instability and MRI findings and based on the inclusion and exclusion criteria. The most common symptom at presentation was instability (36.66%) followed by knee pain (33.33%). Both knee pain and instability were present in 23.33% of patients.